AN ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING LOCAL HISTORY OF WEST KALIMANTAN AT SMK NEGERI 3 PONTIANAK : Analisis Strategi Guru Dalam Mengajarkan Sejarah Lokal Kalimantan Barat di SMK Negeri 3 Pontianak - Andang Firmansyah; Yustinus Rudiyanto; Rio Prayogo (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
This study investigates the pedagogical strategies employed by teachers in delivering local history lessons of West Kalimantan at SMK Negeri 3 Pontianak. The research is primarily motivated by the limited integration of local historical content within the national curriculum, particularly in vocational schools where the emphasis is often placed on practical skills. Utilizing a qualitative case study design, data were collected through semi-structured interviews and comprehensive document analysis involving both history teachers and students. The findings reveal that teachers effectively implement integrative and contextual strategies by linking national historical topics with relevant local content, such as the histories of the Pontianak and Sambas Sultanates. To enhance student engagement, a variety of media are utilized, including PowerPoint presentations, educational videos, and virtual tours to historical sites. However, teachers encounter several challenges, including limited time allocation, insufficient teaching materials, and a lack of adequate institutional support. Despite these constraints, teachers demonstrate remarkable creativity by developing their own materials and employing digital and problem-based learning (PBL) approaches. Consequently, students exhibit positive responses, showing increased motivation and a heightened awareness of their cultural identity. The novelty of this study lies in its illumination of how vocational education successfully integrates local history through innovative digital learning strategies, thereby significantly enhancing students’ historical understanding and fostering local character formation.